Hibriditas Budaya dalam Ketoprak Dor - Suyadi Suyadi (LIPI Press, 2019)
Ketoprak dor is a performing art that lives and develops in North Sumatra. Its appearance began with the sending of Javanese as contract workers for tea plantations. The transmigration of the kuli kontrak formed a new layer of society with the participation of existing social and cultural growth. They did their Javanese activities as usual before being sent as contract coolies, including throwing parties. From this party, there was a desire to make a ketoprak performance. This show is called the ketoprak dor. Based on this, the author conducted a ketoprak dor study in 2009 and 2012 using a semiotic approach by Morris (Zaimar, 2008). The author's semiotic review is done to facilitate the tracking of history and description of the ketoprak dor in North Sumatra Province. From the research that the authors did mention the ketoprak dor is almost extinct swallowed by the times. In fact, the ketoprak dor is actually no longer only owned by Javanese people, but has become the property of Deli Malays. Adapting Javanese people plus Malays who want to accept openness is a big capital of this cultural hybrid process.